Rosuvastatin Reduces Neuroinflammation in the Hemorrhagic Transformation After rt-PA Treatment in a Mouse Model of Experimental Stroke - Lu, Dan; Liu, Yanfang; Mai, Hongcheng; Zang, Jiankun; Shen, Lingling; Zhang, Yusheng; Xu, Anding (Frontiers in Cellular Neuroscience, 2018)
Haemorrhagic transformation (HT) is a serious complication that stimulates inflammation during reperfusion therapy after acute ischaemic stroke. Rosuvastatin, a 3-hydroxymethyl-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor, might improve the outcome of HT by inhibiting neuroinflammation. This study aimed to explore the protective effects of rosuvastatin against HT after recombinant tissue plasminogen activator (rt-PA) treatment in mice with experimental stroke via the attenuation of inﬂammation. A total of one hundred sixty-nine male BALB/c mice were used in the experiment. HT was successfully established in seventy mice that were subjected to 3 hours of middle cerebral artery occlusion (MCAO) followed by a 10 mg/kg rt-PA injection over 10 min and reperfusion for 24 hours. The mice were then administered rosuvastatin (1 mg/kg, 5 mg/kg) or saline (vehicle). The brain water content and neurological deficits (wire hang and adhesive removal somatosensory tests) were assessed at 24 hours after rt-PA reperfusion following MCAO surgery. The morphology, blood-brain barrier (BBB) permeability, and number of astrocytes and microglia were assessed by immunohistochemistry, electron microscopy, and western blotting at 24 hours after rt-PA reperfusion following MCAO surgery. Rosuvastatin protected against impaired neurological function and reversed the BBB leakage observed in the HT group. The increased activation of astrocytes and microglia and secretion of inflammatory factors caused by HT damage were significantly attenuated by high-dose rosuvastatin treatment vs. normal-dose rosuvastatin treatment. Related inflammatory pathways, such as the nuclear factor kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways, were downregulated in the rosuvastatin-treated groups compared with the HT group. In conclusion, our results indicate that rosuvastatin is a promising therapeutic agent for HT after rt-PA reperfusion following MCAO surgery in mice, as it attenuates neuroinflammation. Additionally, high-dose rosuvastatin treatment could have a greater anti-inflammatory effect on HT than normal-dose rosuvastatin treatment.